Pengaruh Perputaran Modal Kerja, Perputaran Kas, dan Perputaran Piutang terhadap Profitabilitas (Studi Empiris pada Perusahaan Ritel Subsektor Supermarket dan Minimarket yang Terdaftar di BEI Periode 2018–2022) - Rezkiawan, Ade Arya (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of working capital turnover, cash turnover, and receivables turnover on profitability in retail companies within the supermarket and minimarket subsector listed on the Indonesia Stock Exchange during the 2018–2022 period. The study employs a quantitative approach using secondary data obtained from quarterly financial statements. The sample was selected through purposive sampling and consisted of five companies with 100 initial observations. After eliminating 57 outlier observations, 43 observations were included in the final analysis. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. The results show that working capital turnover has a negative and significant effect on profitability, cash turnover has a positive and significant effect, and receivables turnover has a negative and significant effect. Simultaneously, working capital turnover, cash turnover, and receivables turnover significantly affect profitability. The adjusted coefficient of determination is 99.9%, indicating that the research model explains 99.9% of the variation in profitability.